Colonizing space and commodifying place: tourism's violent geographies. Issue 5 (4th May 2017) - Devine, Jennifer A.
ABSTRACT: Across Latin America, non-traditional tourism sectors, like eco-tourism and cultural tourism, have grown dramatically in the last 30 years. Neoliberal ideologies, reforms, and infrastructure set the stage for growth, but neoliberalism alone does not explain why the tourism industry is an acute site of struggle over territory, identity and history. From Guatemala's Maya Biosphere Reserve in the heart of Central America's "Mayan World" tourism initiative, this article asks: Why is contemporary tourism such a powerful and pervasive site of contentious socio-spatial politics? It argues that neoliberal reforms have combined with tourism's dual violent practices of spatial colonization and the commodification of place to fuel this growth and politicization. Spatial colonization refers to the commodification of "nature" and practices of land dispossession that define capitalism's expansion into "underdeveloped" and "green" spaces. The industry also commodifies the culture, identity and experience of a place and its people as objects of tourist consumption, which infuses tourism's representational practices with immense, yet subtle power. This article further illustrates how tourism landscapes are carved out of practices of material and intangible dispossession, as well as practices of state territorialization. This violence often engenders diverse forms of resistance by "hosts" living in other people's playgrounds around the world.